KAJIAN FLOKULAN POLIMER ANIONIK DENGAN METODE JAR TEST UNTUK PEMANFAATAN LUMPUR CAIR PT AIR MINUM BANDARMASIH (PERSERODA) - Lailiani, Nurhidayah; Razie, Fakhrur; Biyatmoko, Danang; Lilimantik, Emmy (EnviroScienteae, 2023)
This study aims to identify the characteristics of the liquid sludge produced in IPA 1 A unit Yani PTAM Bandarmasih and analyze the effect of different doses of anionic polymer flocculants on the parameters of the quality standards of the Minister of Health Number 32 of 2017 for sanitary hygiene. This research was carried out using the experimental design experimental method in the Design Randomized Group consisting of 6 (six) treatments. Analysis of the data used includes identifying the characteristics of liquid sludge in situ. Analyzing the effect of different doses of anionic polymer by testing the jar test method with several combination treatments of anionic polymer flocculants on the decrease in parameters according to Permenkes Number 32 of 2017 will be analyzed using analysis of variance. Multiple regression equations to provide information about the relationship between the dependent variable and one or more independent variables used in the study. From the results of the study of Anionic Polymer Flocculants Using the Jar Test Method for Utilizing Liquid Sludge of PT Air Drinking Bandarmasih (Perseroda) it can be concluded that 1) Liquid sludge of PTAM Bandarmasih which has not been managed is still not suitable for sanitation hygiene water because there are several parameters whose values have not been meet the quality standards of Permenkes No. 32 of 2017, 2) After the addition of anionic polymer flocculants, the value of all parameters decreased, but what met the overall quality standard was a dose of 10 ppm.